Primary Fallopian Tube Carcinoma: A Diagnostic Enigma - LO, TK; PODDAR, Nises Chandra (Hong Kong Journal of Gynaecology, Obstetrics and Midwifery, 2023)
A patient with primary fallopian tube carcinoma is reported. The diagnostic options are reviewed and their limitations discussed.